Two Endopolygalacturonase Genes in Trichoderma virens: In Silico Characterization and Expression during Interaction with Plants. Issue 1 (30th May 2015) - Baroncelli, Riccardo; Matarese, Fabiola; Moncini, Lorenzo; Vannacci, Giovanni; Vergara, Mariarosaria
Abstract: The ability of Trichoderma spp. to antagonize most phytopathogenic fungi and to interact with plants by inducing their resistance and promoting their growth has been widely described. Endopolygalacturonases (endoPGs) produced by Trichoderma spp. can assist root penetration and play a pre‐eliciting role in induced systemic resistance (ISR), a beneficial effect detected in plants colonized by Trichoderma . In this study, two endoPG genes ( Tvpg1 and Tvpg2 ) have been identified and partially characterized in a T. virens isolate, previously investigated for its antagonistic ability in several biological systems. An extensive in silico analysis showed relatively low sequence similarities (53%) between TvPG1 and TvPG2 proteins and underscored interesting phylogenetic relationships in the comparison of endoPG genes among fungal genomes. The phylogeny of endoPGs suggests a differentiation in action mechanisms associated with biological functions as one cluster shows only genes from plant‐interacting organisms. A gene expression analysis demonstrated a different regulation pattern for those genes. The Tvpg1 gene was induced both when the fungus was grown in liquid cultures supplemented with pectin or plant cell walls and when it was applied to tomato roots in a growth chamber. Expression times were comparable in both systems. On the contrary, the Tvpg2 gene displayed a constitutive expression in all conditions tested, including controls. The molecular communication between tomato roots and T. virens was investigated by checking the expression of a tomato PGIP ( Lepgip1 ) in roots colonized by fungal mycelium. The Lepgip1 transcript was induced at times coincident with Tvpg1 expression, suggesting a correlation between the two gene products. This paper reports the results of first investigations of T. virens endoPG genes performed on a structural, phylogenetic and functional level.